Respuesta :

36 becomes a negative 

First -36 + -1 -37
Next: -18 + -2 = -20 
Next: -12 + -3 = -15
Next: -9 + -4 which equals -13
Finally we get to the last part: -6 + -6 = -12

We change z2 to [tex] z^{2} [/tex]

[tex] z^{2} [/tex] - 6(z) = 36 

z(z) - 6

Because, we add up for the first two terms

Switch up, up the problem 6(z) - 6

Now, let's add the number 4 on the terms 
z - 6 (z - 6) 

Then, let's multiply z - 6 from z - 6 

[tex] z - 6^{2} = ? [/tex]

From this problem we have to add 6 from the sides that we are working with 

Therefore, your answer for z is 6